Implementation of the STEPPS program for the treatment of self-harm behaviors in Catalonia’s prisons: barriers and facilitators - Rosa Lorente-Català; Irene Jaén; Xavier Buscà-Huertas; Berta Framis; Azucena García-Palacios (BMC Public Health)
Abstract Background The Systems Training for Emotional Predictability and Problem Solving (STEPPS) is an evidence-based program that has been shown to be effective in reducing self-harm behaviors in Correctional Settings (CS). However, there is limited understanding of the contextual factors that impact the implementation of this intervention within such complex environments. A comprehensive understanding of the implementation process is crucial for the successful adoption of this program. This study aims to examine the factors that influence the implementation of the STEPPS program in CS, specifically regarding the management of self-harm behaviors. Method A hybrid implementation effectiveness type III study was conducted in penitentiary centers in Catalonia (Spain). Eight Focus Group Discussions based on the Consolidated Framework for Implementation Research (CFIR) were conducted with 17 professionals who implemented the STEPPS program. Additionally, quantitative data were gathered using an open-closed questionnaire based on a CFIR questionnaire. Results The results indicated that the scientific evidence and knowledge acquired during the implementation process were seen as facilitators. Also, meetings and support from the external research team were considered positive factors. Conversely, implementation barriers of the STEPPS program in CS included the complexity of the intervention format and the mobility of inmates between modules and centers during the duration of the program. Conclusions These findings represent the first attempt to address self-harm behaviors within CS while considering the implementation process. They provide valuable insight into adapting evidence-based interventions, such as STEPPS, for implementation in CS. Trial registration NCT06297460 (ClinicalTrials.gov, retrospectively registered).